PENGARUH SMARTPHONE TERHADAP FREKUENSI MEMBACA ANAK SEKOLAH DASAR - heni amrunaida; Alpian; Chasandra Uccy Lina S; Elsika Yona Putri; M. Indra Almujahid; Maimunah; Ahmad Suriansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of smartphone use on the reading frequency of fifth-grade students at SDN Semangat Dalam 3. The method used is quantitative correlational with a population of 24 students. Data were collected using a Likert scale questionnaire and analyzed using Spearman's rank correlation test. The results showed that the average smartphone usage score was in the medium-high category, while reading frequency was low. The correlation test showed a significant negative relationship (rₛ = −0.40, p = 0.05), which means that the higher the intensity of smartphone usage, the lower the students' reading frequency. These findings were supported by teacher interviews, which revealed that smartphones were used more for entertainment, thereby affecting reading interest. The study highlights the important role of teachers and parents in balancing technology use with literacy habits in order to increase children's reading interest.